2000
DOI: 10.1086/318157
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough Pneumococcal Bacteremia in Patients Being Treated with Azithromycin and Clarithromycin

Abstract: Streptococcus pneumoniae strains have exhibited decreasing susceptibility to penicillins and macrolides during the past several years. We reviewed the medical charts of all patients with pneumococcal bacteremia who were admitted to a university hospital over a period of 1 year, to identify failures of outpatient therapy. Of 41 patients admitted with pneumococcal bacteremia, 4 had previously taken either azithromycin or clarithromycin for 3-5 days. All 4 had pneumococcal strains that exhibited low-level resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
123
2
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(131 citation statements)
references
References 19 publications
4
123
2
2
Order By: Relevance
“…Prior antibiotic therapy was also a significant risk factor for harboring a penicillin and cephalosporin resistant organism. This is consistent with the results of numerous other studies, (7,8,12,25,26) and is not surprising, considering that the selective pressure exerted on organisms by antibiotics, forces species to develop mechanisms of resistance to allow for its survival. These results should be framed in the context that it is likely that the patients included in this study had organisms which were already resistant to the antibiotic prescribed.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Prior antibiotic therapy was also a significant risk factor for harboring a penicillin and cephalosporin resistant organism. This is consistent with the results of numerous other studies, (7,8,12,25,26) and is not surprising, considering that the selective pressure exerted on organisms by antibiotics, forces species to develop mechanisms of resistance to allow for its survival. These results should be framed in the context that it is likely that the patients included in this study had organisms which were already resistant to the antibiotic prescribed.…”
Section: Discussionsupporting
confidence: 92%
“…(5, [16][17][18][19] Despite widespread reports of decreased susceptibility of S. pneumoniae to penicillins, cephelosporins, and macrolides, these remain the most commonly prescribed antibiotics for both children and adults with community acquired pneumonia in the United States and Canada. (4,12) With increasing rates of antibiotic resistance of S. pneumoniae, decisions on treatment of patients with such infections may depend on local antimicrobial susceptibility, as well as clinical outcomes of patients treated with these antibiotics. Prior studies investigating the clinical relevance of antibiotic resistance and mortality in pneumococcal disease have been based on a much smaller number of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Levofloxacin was the least active agent (higher MPC values) by these measurements and it was predicted that levofloxacin was more likely to select for resistant subpopulations than the other agents; of the agents tested, only levofloxacin and moxifloxacin remain in clinical practice. In 2002, Davidson et al [38], reported on the selection of levofloxacin resistant S. pneumoniae in patients infected with this organism and treated with levofloxacin and numerous subsequent reports have identified the same pattern of resistance selection during antimicrobial therapy with macrolides [39][40][41].…”
Section: Measuring Resistancementioning
confidence: 99%